Construction of a Shape‐Diverse Fragment Set: Design, Synthesis and Screen against Aurora‐A Kinase. Issue 27 (26th April 2019) - Zhang, Rong; McIntyre, Patrick J.; Collins, Patrick M.; Foley, Daniel J.; Arter, Christopher; von Delft, Frank; Bayliss, Richard; Warriner, Stuart; Nelson, Adam
Abstract: Historically, chemists have explored chemical space in a highly uneven and unsystematic manner. As an example, the shape diversity of existing fragment sets does not generally reflect that of all theoretically possible fragments. To assess experimentally the added value of increased three dimensionality, a shape‐diverse fragment set was designed and collated. The set was assembled by both using commercially available fragments and harnessing unified synthetic approaches to sp 3 ‐rich molecular scaffolds. The resulting set of 80 fragments was highly three‐dimensional, and its shape diversity was significantly enriched by twenty synthesised fragments. The fragment set was screened by high‐throughput protein crystallography against Aurora‐A kinase, revealing four hits that targeted the binding site of allosteric regulators. In the longer term, it is envisaged that the fragment set could be screened against a range of functionally diverse proteins, allowing the added value of more shape‐diverse screening collections to be more fully assessed. Abstract : A shape‐diverse fragment set was designed and collated to assess experimentally the added value of increased three dimensionality in fragment‐based ligand discovery.